PENGARUH MEDIA SCRAPBOOK UNTUK MENINGKATKAN KETERAMPILAN MEMBACA PEMAHAMAN SISWA KELAS III PADA PEMBELAJARAN BAHASA INDONESIA - Syifa Aulia Hijriyah; Dadan Dadan Djuanda; Dety Amelia Karlina (Jurnal Pena Ilmiah, 2022)
Learning media is a means or a tool to stimulate students to be motivated in learning activities. However, learning media cannot always be used. The use of media must consider the characteristics and behavior of students, as well as the subjects taught. Therefore, this study aims to determine the effect of using scrapbook media on improving reading comprehension skills in third grade elementary school students. This research is a quasi-experimental study with a nonequivalent control group design. A total of 60 third grade elementary school students at two different schools were sampled in this study. The results of the analysis show that the application of scrapbook media has an effect on increasing reading comprehension skills with a sig value. 0.000 0.05. The improvement of reading comprehension skills in the group using scrapbook media gave more optimal results than the group that did not apply scrapbook media. Student responses to the application of scrapbook media stated that this media was very helpful in understanding the contents of the reading because it was easy to understand, interesting and gave pleasure when using scrapbook media.